Existence and limit behavior of constraint minimizers for elliptic equations with two nonlocal terms - Xincai Zhu; Yajie Zhu (Electronic Research Archive)
This paper is devoted to studying constraint minimizers for a class of elliptic equations with two nonlocal terms. Using the methods of constrained variation and energy estimation, we analyze the existence, non-existence, and limit behavior of minimizers for the related minimization problem. Our work extends and enriches the study of bi-nonlocal problems.